Water distribution in an arid zone soil: Numerical analysis of data from a large weighing lysimeter - Dijkema, J.; Koonce, J. E.; Shillito, R. M.; Ghezzehei, T. A.; Berli, M.; Van Der Ploeg, M. J.; Van Genuchten, M. Th. [UNESP] (Wiley, 2018)
Although desert soils cover approximately one third of the Earth’s land surface, surprisingly little is known about their physical properties and how those properties affect the ecology and hydrology of arid environments. The main goal of this study was to advance our understanding of desert soil hydrodynamics. For this purpose, we developed a process-based component within HYDRUS-1D to describe the moisture dynamics of an arid zone soil as a function of water fluxes through the soil surface. A modified van Genuchten model for the dry end of the soil water retention curve was developed to better capture the basic flow processes for very dry conditions. A scaling method was further used to account for variabilities in water retention because of changes in the bulk density vs. depth. The model was calibrated and validated using hourly soil moisture, temperature, and mass data from a 3-m-deep weighing lysimeter of the Scaling Environmental Processes in Heterogeneous Arid Soils facility at the Desert Research Institute (Las Vegas, NV). Measurements and simulations during a 1-yr period agreed better under precipitation (wetting) than under evaporation (drying) conditions. Evaporation was better simulated for wet than for dry soil surface conditions. This was probably caused by vapor-phase exchange processes with the atmosphere, which were unaccounted for and need to be further explored. Overall, the model provides a promising first step toward developing a more realistic numerical tool to quantify the moisture dynamics of arid ecosystems and their role in climate change, plant growth, erosion, and recharge patterns.